Wrongdoing by results: Moore's experiential argument - Gardner, J (Cambridge University Press, 2012)
Michael Moore and I agree about the moral importance of how our actions turn out. We even agree about some of the arguments that establish that moral importance. In Causation and Responsibility, however, Moore foregrounds one argument that I do not find persuasive or even helpful. In fact I doubt whether it even qualifies as an argument. He calls it the "experiential argument." In this comment I attempt to analyze Moore's "experiential argument" in some detail and thereby to bring out why it does not help. In the process I raise some problems about the rationality of the emotions, which may be where Moore and I part company. We both believe that emotions should be taken more seriously by moral philosophy. But apparently we have radically different views about what this means. © Cambridge University Press 2012.